Dose escalation of osimertinib for intracranial progression in EGFR mutated non-small-cell lung cancer with brain metastases. Issue 1 (24th September 2020) - Goldstein, Iris M; Roisman, Laila C; Keren-Rosenberg, Shoshana; Dudnik, Julia; Nechushtan, Hovav; Shelef, Ilan; Fuchs, Vered; Kian, Waleed; Peled, Nir
Abstract: Background: Osimertinib is a selective irreversible epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) with increased penetration across the blood–brain barrier compared with previous EGFR-TKIs, and thus, a 52% reduction in the risk of intracranial disease progression is seen when it is used as a first line of therapy compared with gefitinib and erlotinib. It is also efficient as second-line therapy for patients who developed the T790M resistance mutation following treatment with previous generation TKIs. Here, we report 11 patients who were treated by an increasing dose of osimertinib from 80 mg to 160 mg QD orally following intracranial progression in either first- or second-line setting. Methods: This is a subcohort analysis from a larger nonrandomized, phase 2, open-label trial, evaluating the efficacy of osimertinib dose escalation from 80 mg to 160 mg in EGFR-mutated advanced non-small-cell lung cancer (NSCLC) patients with intracranial progression in either first- (arm A) or second-line setting (arm B for T790M+ and C for T790M−). Results: Eleven patients, 5 in arm A, 4 in arm B, and 2 in arm C were reported in this study. The mPFS of osimertinib before dose escalation was 11.4 ± 8.9 (6.6–30.7) months for arm A, 8.7 ± 1.8 (6.3–11.2) for arm B, and 14.5 ± 7.8 (6.7–22.3) for arm C. Intracranial response rate to dose escalation was 54% (6 of 11) with 2 of 11 having intracranial stability. Median iPFS was 4.3 ± 7.4 (0.7–25.5) months; 3.8 ± 6.4 (1.8–18.9), 5.6 ± 9.7 (0.7–25.5), and 7.0 ± 2.7 (4.3–9.6) for arms A/B/C, respectively. Dose escalation was well tolerated with diarrhea and paronychia as the main dose-limiting symptoms. Conclusions: Osimertinib 160 mg is feasible and may offer a therapeutic alternative for patients with isolated intracranial progression on osimertinib standard (80 mg) dose. Further studies on CNS osimertinib pharmacokinetics are needed to test this hypothesis.